Myoepithelioma of bone with a novel FUS‐POU5F1 fusion gene. Issue 6 (31st October 2014) - Puls, Florian; Arbajian, Elsa; Magnusson, Linda; Douis, Hassan; Kindblom, Lars‐Gunnar; Mertens, Fredrik
<x xml:space="preserve">Abstract</x> Aims Myoepithelial tumours of soft tissue are rare lesions with a broad morphological and clinical spectrum. Previous studies have found EWSR1 rearrangements in approximately half of all cases and PBX1, ZNF44 and POU5F1 have been identified as recurrent fusion partners. In bone, only a small number of myoepithelial tumours have been described. We investigated an intraosseous myoepithelioma of the sacrum in a 54‐year‐old man without EWSR1 rearrangement for the presence of other fusion genes. Methods and results G‐banding analysis, SNP‐array and fluorescence in situ hybridisation suggested rearrangement of the FUS and POU5F1 genes. RT‐PCR confirmed a chimeric in‐frame transcript fusing FUS exon 5 to POU5F1 exon 2. The clinical course after en bloc resection was without recurrence or metastasis over a period of 87 months. Conclusion We report a novel FUS‐POU5F1 fusion gene in an intraosseous myoepithelioma of the sacrum. This case highlights that FUS can replace EWSR1 as the N‐terminal transactivator in oncogenic fusion genes in myoepithelial tumours, similar to that which has previously been demonstrated in other tumour entities. Thus, in addition to EWSR1, also FUS needs to be considered as a potential fusion partner in the molecular work up of myoepithelial tumours.